Structure, evolution and dynamics of gene regulatory networks - Babu, M. Madan (Henry Stewart Talks, 2012)
Regulatory genomics and systems biology, Transcriptional networks, Network motifs, Scale-free networks, How transcriptional networks evolve, Mechanisms for the creation of new genes, Gene duplication and network growth, Evolution of local network structure, Gene regulatory network and expression data, Back-tracking method to find active sub-networks -Temporal dynamics of local & global structure, Topological properties, Dynamic properties, Hierarchical organisation in networks & of regulatory proteins, Noise in protein levels, Non-genetic variation, Phenotypic variability in fluctuating environments, Differential cell-fate outcome, Node dynamics
Reviewed at 2016/11/01